Analisis Teori Antrian dan Optimalisasi Pelayanan Pada Alfamart Perum Cengkong Menggunakan Model Single Channel-Single Phase - Dimas Darma Kusuma; Wahyudin Wahyudin; Ahmad Anshari (Fakultas Teknik, 2023)
Alfamart is a minimarket in which there is a service to consumers, therefore services must be considered and taken into account for consumer convenience. The purpose of this study is to see how optimal the service is at the Alfamart branch of Perum Cengkong. Alfamart Perum Cengkong uses a Single Channel-Single Phase queuing system. The results of this study were that by testing the normality of the data using the Statistical Program for Social Science (SPSS) software, the results of testing using the 1-Sample Kolmogorov-Smirnov showed that the positive deviation value was 0.215, the negative deviation was -0.167, while the Asymp, Sig values were 0.000. Then the data on the number of buyers is normally distributed because 0.000 ≤ 0.05. Furthermore, the Single Channel-Single Phase queuing model is very appropriate to use because buyers can be served well and get optimal time. This can be seen from the number of individuals or buyers waiting in the queue (Lq), which is 0.003. The average number of buyers in the system (L) totals 0.06. The probability of having no buyers or empty servers (P0) is 94%.